MODEL PEMBELAJARAN PENDIDIKAN VOKASIONAL YANG EFEKTIF DI ERA REVOLUSI INDUSTRI 4.0 - Arya Putra (CV. ADIBA AISHA AMIRA, 2025)
Eflective vocational education learning model in the era of industrial revolution 4.0 is one of the important themes in vocational education. Vocational education needs to adapt to industry changes and develop eflective strategies to adapt to the Industrial Revolution 4.0. The eflective learning model of vocational education in the era of the industrial revolution 4.0 is a necessary concept in vocational education. This model contributes to the creation of specialized training that meets the needs of the department and adapts to changes in the department. The model uses concepts adapted to the Industrial Revolution 4.0, such as digital concepts and information and communication technology (ICT).